Bottom‐up control of parasites. Issue 10 (5th October 2017) - Johnson, David Samuel; Heard, Richard
Abstract: Parasitism is a fundamental ecological interaction. Yet we understand relatively little about the ecological role of parasites compared to the role of free‐living organisms. Bottom‐up theory predicts that resource enhancement will increase the abundance and biomass of free‐living organisms. Similarly, parasite abundance and biomass should increase in an ecosystem with resource enhancement. We tested this hypothesis in a landscape‐level experiment in which salt marshes (60, 000 m 2 each) received elevated nutrient concentrations via flooding tidal waters for 11 yr to mimic eutrophication. Nutrient enrichment elevated the densities of the talitrid amphipod, Orchestia grillus, and the density and biomass of its trematode parasite, Levinseniella byrdi . Strikingly, L. byrdi prevalence increased over time, up to 13 times higher in nutrient‐enriched marshes (30%) relative to the mean prevalence in reference marshes (2.4%). The biomass density of infected amphipods was, on average, 11 times higher in nutrient‐enriched marshes (1.1 kg/ha) than in reference marshes (0.1 kg/ha), when pooling across all years. Orchestia grillus biomass comprises 67% of the arthropod community biomass; thus, nutrient enrichment elicits a substantial surge in parasitized biomass in the arthropod community. If our results are typical, they suggest that eutrophication can increase parasite abundance and biomass with chronic resource enhancement. Therefore, minimizing aquatic nutrient pollution may prevent outbreaks of parasites with aquatic hosts.